Agriculture and Central Physical Grid Intrasructure - Lipton, Michael (International Food Policy Research Institute, 1987)
Sub-Saharan Africa faces the following dilemma. Growth in agriculture is often held back by inadequate transport, communications, power, and other centralized physical grid infrastructure (CPGI). But investment in such infrastructure is increasingly eating up savings resources. This tends to compel reductions in agricultural investment-which, however, is a necessary complement to CPGI investment as a source of agricultural growth. To make things worse, inputs per worker other than capital are frequently of low quality and improving only slowly. Hence there is only slow growth of output per worker and thus of domestic savings to be invested in future growth. As we shall see, current and proposed levels of investment in CPGI would raise dependence on foreign savings to unacceptable levels, yet leave too little total savings to finance even minimally acceptable levels of net investment in productive capital.